Adoption from care : international perspectives on children's rights, family preservation and state intervention - Pösö, Tarja; Skivenes, Marit (Research in social work (Policy Press), 2021)
EPDF and EPUB available Open Access under CC-BY-NC-ND. This book explores how children's rights are practised and weighed against birth and adoptive parents' rights and examines how governments and professionals balance rights when it is decided that children cannot return to parental care. From different socio-political and legal contexts in Europe and the United States, it provides an in-depth analysis of concepts of family, contact, the child's best-interest principle and human rights when children are adopted from care. Taking an international comparative approach to these issues, this book provides detailed information on adoption processes and shares learning from best practice and research across country boundaries to help improve outcomes for all children in care for whom adoption may be the placement of choice.EPDF and EPUB available Open Access under CC-BY-NC-ND. This book explores how children's rights are practised and weighed against birth and adoptive parents' rights and examines how governments and professionals balance rights when it is decided that children cannot return to parental care. From different socio-political and legal contexts in Europe and the United States, it provides an in-depth analysis of concepts of family, contact, the child's best-interest principle and human rights when children are adopted from care. Taking an international comparative approach to these issues, this book provides detailed information on adoption processes and shares learning from best practice and research across country boundaries to help improve outcomes for all children in care for whom adoption may be the placement of choice.